Efeitos do treinamento resistido/musculação nos indicadores de sarcopenia e obesidade sarcopênica em idosos - Pinheiro, Jéssica da Silva (2021)
Human aging has become an increasingly relevant issue and addressed worldwide because, for the first time in history, in 2018, the number of elderly people aged 60 years and over reached rates higher than the number of children under 5 years of age. Given this context, studies show that there is an expectation that one in six people in the world will be over 65 years old by 2050. In this context, sarcopenia is quite prevalent in this population. This is a syndrome characterized by the gradual and general loss of muscle mass, reduced strength and body functionality. An important subgroup of this audience is now classified as having sarcopenic obesity, reported as a high-risk geriatric syndrome in the elderly with synergistic complications of sarcopenia and obesity. In order for this loss process to be curbed or mitigated, it is essential to maintain physical fitness, physical exercise, in particular, resistance training/weight training. Thus, the aim of this study was to verify the effects of resistance training/weight training on indicators of sarcopenia and sarcopenic obesity in the elderly. This study is part of an umbrella project entitled “Interdisciplinary approach to the rehabilitation of aging individuals with musculoskeletal disorders”. Initially, it would be carried out experimentally, but as a result of the covid-19 pandemic in Brazil, which suspended the carrying out of experimental studies with the elderly in our city, as this is a population that is part of the risk group for the disease , we chose to try to answer the proposed objectives through two productions of the systematic review type and in accordance with the recommendations proposed by the Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist. To search for studies on the proposed topic, both in production I and in production II, the databases Web of Science, Medline / Pubmed, LILACS and Scielo and PEDro were used. Inclusion criteria were: (1) clinical trial studies; (2) studies carried out with elderly people in the community; (3) studies that verified the effects of resistance training (RT) with gym machines and/or free weights; (4) studies involving one or more sarcopenia indicators (muscle strength, muscle mass and physical function), in both productions it was evaluated on sarcopenic obesity and studies that included the percentage of body fat. The initial sample consisted of 530 articles, and at the end 2 articles were part of production I. In production II, 6 articles were included. Only one search was performed, because in the MeSH (Medical Subject Headings) the descriptor “sarcopenic obesity” does not exist, this is a pathology that is part of sarcopenia and obesity together. After analyzing the results, it was observed that there is still a shortage of studies on the effects of resistance training/weight training in elderly people with these syndromes and there is a great need for greater study designs and samples, as well as greater depth. However, there seems to be a consensus in the literature that resistance training with weight training is beneficial to improve sarcopenia and sarcopenic obesity.